ANALISA PERBANDINGAN REALISASI BIAYA ANTARA PERENCANAAN DAN PELAKSANAAN PEKERJAAN STRUKTUR PONDASI BOR PILE GEDUNG INKULTURATIF GBKP BUKIT KEC. BERASTAGI - Darnianti, Darnianti; Christy, Julieta; Laia, Fiber Jean Smara; Vernando W, Jeremi Liliteo (Universitas Quality, 2024)
The location for the construction of the GBKP Bukit Inculturative Building, Berastagi sub-district, is a high-risk location because it is located in an area prone to earthquakes, high ground and prone to landslides. Construction of the GBKP Bukit District Inculturative Building. Berastagi was created as a place of worship which is filled with worshipers every day. Therefore, the planning and construction of the type of substructure (foundation) needs to be carefully calculated so that the building does not subside or collapse. The purpose of this research is to determine the cost comparison between planning and implementation costs for drill pile foundation work in the field and to determine the carrying capacity of the drill pile foundation on the GBKP Bukit District Inculturative Building construction project. Berastagi, knowing the dimensions of the reinforcement used in the foundation of the GBKP Bukit Kec Inculturative Building. Berastagi and knowing the method of carrying out construction work and the planned cost budget (RAB) for the drill pile foundation at the GBKP Bukit Inculturative Building, Berastagi District. This research is planned to target outputs in the Juitech Journal, as mandatory outputs and the results of this research will produce additional outputs in the form of teaching materials and will also be discussed before publication. The Technology Readiness Level (TKT) of the proposed research is at level 2 where analysis is carried out by comparing the planning cost plans and treatment cost budgets in the field.